Kajian Rancangan Irigasi Pipa Sistem Gravitasi - Wildan Herwindo; Dadan Rahmandani (Balai Teknik Irigasi, 2013)
Pipeline irrigation is an alternative in application of irrigation technology that theoretically has a higher efficiency than open channel irrigation. In application, a highly irrigation efficiency can only be achieved if pipeline irrigation designed and operated properly. Laboratory test shows that to dissolve sediment, flow velocity in pipe is recommended at least 0.5 m/sec. The result shows that on farm scale pipeline irrigation using gravitation in Cikurubuk, Buahdua Sub District, Sumedang District needs to pay attention to: (i) capturing consists of 3 (three) parts of the sediment trap, intake, and safety (strainer and overflow), (ii) intake discharge, water quality, and operation system (iii) pipeline system consisting primary, secondary, and tertiary must take into pipe depth, pipe fittings, and thrust block, (iv) complementary component of the pipeline irrigation system aims to keep it functioning properly. Complementary components consists of valve and drain valves, air vent, pressure gauge, water meter, and pressure release.